PENGARUH KUALITAS, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK INDOMIE - Vita Amanda Yuniasari; Diyah Lestariawati; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the influence of product quality, promotion, and price on purchasing decisions for Indomie products. The method used is a quantitative approach through a survey of 97 respondents, where the results of the regression analysis show that simultaneously the three variables have a significant effect on purchasing decisions, but partially only product quality and price have a significant effect, while promotion has no significant effect, so it is concluded that in purchasing decisions for Indomie, consumers consider aspects of quality and price suitability more than promotional intensity, the implications of which can be a strategic evaluation material for business actors in formulating a more effective and relevant marketing approach to today's consumer behavior.